2019
DOI: 10.1002/hep4.1331
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Gut–Liver Axis in Liver Inflammation, Fibrosis, and Cancer: A Special Focus on the Gut Microbiota Relationship

Abstract: The gut and the liver are anatomically and physiologically connected, and this “gut–liver axis” exerts various influences on liver pathology. The gut microbiota consists of various microorganisms that normally coexist in the human gut and have a role of maintaining the homeostasis of the host. However, once homeostasis is disturbed, metabolites and components derived from the gut microbiota translocate to the liver and induce pathologic effects in the liver. In this review, we introduce and discuss the mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
118
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(125 citation statements)
references
References 126 publications
(161 reference statements)
0
118
0
7
Order By: Relevance
“…The most likely scenario is via the gut-liver axis. Many studies have shown that the bacteria and bacterial products can reach the liver through the portal vein and liver secretory products, such as bile acids, IgA, and antimicrobial molecules, can leave the liver into the intestines through the biliary tract 40,41 . It is thus likely that infectious virus exits the liver through the biliary tract into the intestine where it exits the body in the stool, explaining the high stool titers with little to no infectious virus in the intestine itself.…”
Section: Despite the Clear Hepatic Tropism Of Echoviruses Little Is mentioning
confidence: 99%
“…The most likely scenario is via the gut-liver axis. Many studies have shown that the bacteria and bacterial products can reach the liver through the portal vein and liver secretory products, such as bile acids, IgA, and antimicrobial molecules, can leave the liver into the intestines through the biliary tract 40,41 . It is thus likely that infectious virus exits the liver through the biliary tract into the intestine where it exits the body in the stool, explaining the high stool titers with little to no infectious virus in the intestine itself.…”
Section: Despite the Clear Hepatic Tropism Of Echoviruses Little Is mentioning
confidence: 99%
“…The liver is directly exposed to gut microbial components and metabolites via the liver portal vein ( 26 ). Increasing studies show that the gut–liver axis influences the progression of liver diseases such as liver inflammation, fibrosis, cirrhosis, and cancer ( 27 , 28 ). For instance, high-alcohol-producing bacterium Klebsiella pneumoniae is implicated in the pathogenesis of NAFLD in human patients, evidenced by oral gavage of a clinically isolated strain causing NAFLD in mice ( 29 ).…”
Section: The Roles Of Gut Microbiota In Liver Cancermentioning
confidence: 99%
“…Gut microbiota component and their metabolites affect both hepatocytes and stromal cells (hepatic stellate cells and Kupffer cells). [24] Intestinal dysbiosis is observed in different chronic hepatic diseases; which increased concern about its role in the development and progression of hepatic diseases with aggravation of liver disease-related complications. [25][26] Few studies evaluated the role of gut dysbiosis in patients with viral hepatitis.…”
Section: Variablesmentioning
confidence: 99%